2014
DOI: 10.1002/jbmr.2423
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Recent Spinal Cord Injury on Wnt Signaling Antagonists (Sclerostin and Dkk-1) and Their Relationship With Bone Loss. A 12-Month Prospective Study

Abstract: Spinal cord injury (SCI) has been associated with a marked increase in bone loss and bone remodeling, especially short-term after injury. The absence of mechanical load, mediated by osteocyte mechanosensory function, seems to be a causative factor related to bone loss in this condition. However, the pathogenesis and clinical management of this process remain unclear. Therefore, the aim of the study was to analyze the effect of recent SCI on the Wnt pathway antagonists, sclerostin and Dickkopf (Dkk-1), and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 48 publications
1
22
1
Order By: Relevance
“…Thus, patients with increased P1NP serum values >140 ng/ml presented a 3.08-fold increased risk for osteoporosis development, with a similar figure in patients with bone ALP values >14 ng/ml, who presented a 2.4-fold increased risk. These results are consistent with the marked increase in bone turnover that has been described after injury, especially during the first year of injury coinciding with the highest bone loss that seems to occur during the first 1-2 years after SCI [1,2,[16][17][18][19][20][21]. Nevertheless, although patients who developed osteoporosis presented higher values of both markers, which were also risk factors for osteoporosis development, their evaluation did not seem to add significant clinical value for predicting osteoporosis development in our study, since BMD evaluation alone identified nearly all the patients who would develop osteoporosis during the 12-month period.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Thus, patients with increased P1NP serum values >140 ng/ml presented a 3.08-fold increased risk for osteoporosis development, with a similar figure in patients with bone ALP values >14 ng/ml, who presented a 2.4-fold increased risk. These results are consistent with the marked increase in bone turnover that has been described after injury, especially during the first year of injury coinciding with the highest bone loss that seems to occur during the first 1-2 years after SCI [1,2,[16][17][18][19][20][21]. Nevertheless, although patients who developed osteoporosis presented higher values of both markers, which were also risk factors for osteoporosis development, their evaluation did not seem to add significant clinical value for predicting osteoporosis development in our study, since BMD evaluation alone identified nearly all the patients who would develop osteoporosis during the 12-month period.…”
Section: Discussionsupporting
confidence: 92%
“…This finding may be partly explained by the lack of studies identifying patients with a high risk for developing osteoporosis especially short-term after injury, when the highest bone loss is produced [10,11]. Indeed, in a prospective follow-up study in patients with recent complete SCI, we observed the development of osteoporosis in more than 50 % of subjects within the first year after injury [2]. Therefore, it seems logical to assume that the identification of high-risk patients for osteoporosis short-term after injury would improve the therapeutic approach to this clinical complication.…”
Section: Introductioncontrasting
confidence: 51%
See 3 more Smart Citations